1986
DOI: 10.1139/x86-089
|View full text |Cite
|
Sign up to set email alerts
|

Variation in seed set and proportions of outcrossed progeny with clones, crown position, and top pruning in a Douglas-fir seed orchard

Abstract: The effects of clonal variability, crown position of cones, and top pruning on the proportions of viable outcrossed progeny [Formula: see text] and filled seeds (PF) were investigated in a 20-year-old Douglas-fir (Pseudotsugamenziesii (Mirb.) Franco) seed orchard. Estimates of [Formula: see text] were derived by means of a maximum likelihood procedure from data from 10 allozyme loci. Values for [Formula: see text] and PF were significantly heterogeneous (P < 0.05) among six selected clones for all pruning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 0 publications
4
18
0
Order By: Relevance
“…Spatial separation of male and female flowers or variation in flowering phenology should also influence the rate of self-fertilization. Omi & Adams (1986) explain all the selfing variation, the 'inherent selffertility' was also considered to play a significant role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial separation of male and female flowers or variation in flowering phenology should also influence the rate of self-fertilization. Omi & Adams (1986) explain all the selfing variation, the 'inherent selffertility' was also considered to play a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…The production of male and female flowers in the same individual and the absence of a prezygotic self-incompatibility system make considerable self-fertilization possible. Temporal and spatial isolation of male and female function can prevent selfing in conifers to some degree but not completely (Chung, 1981;Omi & Adams, 1986;Erickson & Adams, 1990). If the concentration of the tree's own pollen around a crown is high, the probability of selfpollination is also expected to be high.…”
Section: Introductionmentioning
confidence: 99%
“…However, no signifi cant correlation was found between the characteristics outcrossing rate and percentage of empty seeds or percentage of full seeds (Sorensen 1971, Schroeder 1989, Kormutak and Lindgren 1996, Freytag 1998, Siregar 2000. It has been suggested that the relation would probably be clearer, when genetic load is the main factor affecting the mating system (Omi and Adams 1986). …”
Section: Relationship Between Percentage Of Empty Seeds and Genetic Fmentioning
confidence: 99%
“…A mixed-mating model, including selfand cross-fertilisation probabilities only, has often been applied in forest trees (Müller-Starck, 1982b;Ritland and El-Kassaby, 1985 Omi and Adams, 1986) and from tree to tree (Erickson and Adams, 1990). Reproductive phenology was a major component determining selfing (Erickson and Adams, 1989 (Prat, 1995).…”
Section: Mating Systemmentioning
confidence: 99%
“…Self-fertilisation may substantially reduce genetic gains (Sorensen, 1982;Sorensen and White, 1988). Various studies of clonal Douglas fir seed orchards, carried out in the natural range of the species, have generally revealed a low selfing level (Omi and Adams, 1986;Erickson and Adams, 1990). However significant levels of contamination by exogenous pollen occur because of the proximity of natural populations (El-Kassaby and Ritland, 1986;Fast et al, 1986; Adams and Birkes, 1991).…”
Section: Introductionmentioning
confidence: 99%